Declaración del XII Congreso de la Asociación Latinoamericana de Medicina Social (ALAMES) - Heredia, Nila; Feo, Oscar; Noronha, José; González, Rafael (Revista Cubana de Salud Pública, 2015)
Declaración del XII Congreso de la Asociación Latinoamericana de Medicina Social (ALAMES)